EVALUASI KINERJA REKSADANA BERDASARKAN METODE SHARPE, TREYNOR, JENSEN, DAN M2? - Bahtiar Usman; indri Ratnasari (Media Riset Bisnis & Manajemen, 2004)
The aim of the research is about the evaluation on mutual funds performance based on Sharpe, Treynor, Jensen, and M? measurement is, it is also to explain the performance of mutual funds (or investment funds) so it can be a consideration factor in investment decision. To invest on mutual funds, investors should be compared knowing their investment compo- sition policy and measurement of their performances. The methods of measurement used in evaluating mutual funds performances are 4 methods of Risk-Adjusted Performance Measures; they are The Sharpe Measurement (RVAR), The Treynor Measurement (RVOL), Jensen's Differential Return (Alpha), and M'. Coefficient determination is used to know which mutual fund has the best diversification. The sample in is 20 mutual funds with 5 years periods after the monetary crisis, from 1999 to 2003. Bench- mark for each type of mutual funds is needed to be a performance comparison. The results based on 4 methods shows the different appraisals and ranks. However, in general, there's only one mutual fund that has the best or optimal performance, which Is Panin Dana Maksima from equity fund.